STUDENTS’ LANGUAGE ATTITUDES TOWARDS THE ACQUISITION OR MAINTENANCE OF HERITAGE LANGUAGE; A CASE STUDY - Nufus, Tatu Zakiyatun (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
Language attitude is one of the most important things in learning a language. It determines students’ seriousness towards language acquisition. this research investigates students’ language attitudes towards their heritage language and other languages that they acquire and learn. The study used a qualitative approach with descriptive analysis, the participants are about 20 students with different languages. The questionnaire and interview consist of heritage and cultural items. This study investigated the students’ language attitude towards their heritage language and other languages they acquire and learn and how valuable are those languages to them. The result demonstrates that students’ language attitudes toward the acquisition or maintenance of heritage language among students are relatively good. They use foreign languages (Arabic and English) in daily communication on a weekday, while the heritage language is used only on their holiday when they meet with parents and another family, to support other language acquisition, the school establish a language policy that relates to language use at that school. In maintaining the heritage language, the students use it in their home to interact with family members during holidays from school activities. Finally, the study above has wide pedagogical implications for learning and teaching language for students, it implies that teaching language to students should be in line with students’ needs. And the use of heritage language and foreign-language should be balanced among them, therefore, the student’s language attitudes will grow faster and better.